The known unknowns of the Hsp90 chaperone - Laura-Marie Silbermann; Benjamin Vermeer; Sonja Schmid; Katarzyna Tych (eLife)
Molecular chaperones are vital proteins that maintain protein homeostasis by assisting in protein folding, activation, degradation, and stress protection. Among them, heat-shock protein 90 (Hsp90) stands out as an essential proteostasis hub in eukaryotes, chaperoning hundreds of ‘clients’ (substrates). After decades of research, several ‘known unknowns’ about the molecular function of Hsp90 remain unanswered, hampering rational drug design for the treatment of cancers, neurodegenerative, and other diseases. We highlight three fundamental open questions, reviewing the current state of the field for each, and discuss new opportunities, including single-molecule technologies, to answer the known unknowns of the Hsp90 chaperone.